2021
DOI: 10.3389/fmicb.2021.670684
|View full text |Cite
|
Sign up to set email alerts
|

Cocultivation Study of Monascus spp. and Aspergillus niger Inspired From Black-Skin-Red-Koji by a Double-Sided Petri Dish

Abstract: Cocultivation is an emerging and potential way to investigate microbial interaction in the laboratory. Extensive researches has been carried out over the years, but some microorganism cocultivation are not easy to implement in the laboratory, especially the fungus-fungus (FF) cocultivation, owing to the obstacles such as fungal different growth rate, limited growing space, hyphae intertwining, and difficulty of sample separation, etc. In this research, a double-sided petri dish (DSPD) was designed and carried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…This was supposed to be one of the reasons for the lower higher alcohols production in the original liquor produced by ERH, because the higher alcohols in Baijiu were mainly produced by yeast through the Ehrlich and Harris pathways ( Cheng et al, 2011 ; Wang et al, 2020 ). Yuan and Chen (2021) found that Aspergillus niger significantly inhibited the growth of Monascus when they were cocultured, and Wang et al (2012) found that yellow pigment produced by Monascus strongly inhibited the spore formation of A. niger . Both Monascus and Aspergillus were dominant genera in TQ, and they competed with each other for nutrients and growth space, demonstrating that the balance between different microbial species was crucial for flavor substances in LATB.…”
Section: Discussionmentioning
confidence: 99%
“…This was supposed to be one of the reasons for the lower higher alcohols production in the original liquor produced by ERH, because the higher alcohols in Baijiu were mainly produced by yeast through the Ehrlich and Harris pathways ( Cheng et al, 2011 ; Wang et al, 2020 ). Yuan and Chen (2021) found that Aspergillus niger significantly inhibited the growth of Monascus when they were cocultured, and Wang et al (2012) found that yellow pigment produced by Monascus strongly inhibited the spore formation of A. niger . Both Monascus and Aspergillus were dominant genera in TQ, and they competed with each other for nutrients and growth space, demonstrating that the balance between different microbial species was crucial for flavor substances in LATB.…”
Section: Discussionmentioning
confidence: 99%
“…The pigments groups concentration was measured using a UV−vis UV-1700 spectrophotometer (Shimadzu, Tokyo, Japan) at 380, 470 and 520 nm which are the maximal absorption of yellow, orange, and red pigments, respectively. The results were expressed as optical density (OD) units per gram of dried mycelia multiplied by a dilution factor [15].…”
Section: Mps and Cit Analysesmentioning
confidence: 99%
“…In addition to its potential clinical benefit, it is worth noting that Monascus sp. has also been used as a starter culture in traditional Chinese fermented foods (e.g., Monascus rice wine, Monascus vinegar, and red fermented bean curd) for over 1000 years [ 3 ]. Ren et al successfully isolated and screened 35 fermentation starters among the Monascus strain FJMR24 with high amylase activity and high glucoamylase activity, resulting in outstanding fermentation adaptability in the process of rice wine brewing [ 4 ].…”
Section: Introductionmentioning
confidence: 99%